(untitled) (Homoeopathy for All, 2024)
Caffeine, common in coffee and tea, can boost alertness but also trigger anxiety, especially in sensitive individuals. This paper explores how caffeine affects the nervous system, potentially worsening anxiety symptoms, and discusses strategies like moderation and mindful consumption to manage these effects and support mental health.